KEJADIAN COVID-19 BERDASARKAN KARAKTERISTIK PENGUNJUNG POLI ISPA PUSKESMAS PERAMPUAN LOMBOK BARAT - Kristiani Kisid; Endy Bebasari Ardhana Putri (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2021)
The Covid-19 pandemic, which began in early 2020, has affected more than 3 million people in Indonesia. All health services are mobilized for p revention and treatment. The Public Health Center of Perampuan in West Lombok is no exception, which carries out a screening program for suspected visitors as visitors. In mid-2021, when a new variant of covid-19 emerged, namely the delta variant, visitors to the Poli ISPA were known to experience an increase in their covid-19 status through the Rapid Diagnostic Test (RDT) antigen. The purpose of this study was to describe the characteristics of poly ISPA visitors who received a COVID-19 swab examination and to find out whether there was a relationship between these characteristics and the incidence of Covid-19 at the Perampuan Health Center. The research design is descriptive retrospective because it uses secondary data from the registration book of Poli ISPA in Public Health Center of Perampuan. A total of 183 samples were taken from the total population, namely those who received an RDT antigen swab examination. The statistical analysis test used to find the relationship was the chi square test (?=5%). The result of this research is that most of the characteristics of the visitors to the ARI poly at the Perampuan Health Center are mostly in the age group category of 18 years and over, working as employees both public and private, and male. The number of cases of covid-19 there is 52%. The conclusion of this study is that there is no relationship between all characteristics of visitors to the ARI polyclinic as measured by the incidence of Covid-19 at the Perampuan Public Health Center (p>0.05). It is better if the Perampuan Health Center continues to carry out the program for handling and preventing this COVID-19 disease because this disease attacks all levels of society equally regardless of age, gender, and type of work. Keywords: Covid-19, Public health center, age, sex